2017
DOI: 10.1021/acsami.7b02365
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Recovery of Organic Transistor Memories with Photoactive Floating-Gate Interlayers

Abstract: Optical memories based on photoresponsive organic field-effect transistors (OFETs) are of great interest due to their unique applications, such as multibit storage memories and flexible imaging circuits. Most studies of OFET-type memories have focused on the photoresponsive active channels, but more useful functions can be additionally given to the devices by using floating gates that can absorb light. In this case, effects of photoirradiation on photoactive floating-gate layers need to be fully understood. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 55 publications
(91 reference statements)
4
126
0
Order By: Relevance
“…Previous studies demonstrated that light illumination could generate excitons in the semiconductor layer of OFET memory devices, which can assist the programming/erasing operation with or without external voltage bias. [9,49,50] Therefore, in the erasing process we utilized a white light with light intensity of about 5 mW cm −2 to illuminate the memory device. It was found that the transfer curve shifted back to its initial position (defined as the erased state) after the WG 3 NSs device was illuminated for 1 s. Memory window (ΔV TH ) is an important parameter for memory devices, which is defined as the difference between V TH in the programmed and the erased states.…”
Section: Field-effect Transistor Memorymentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that light illumination could generate excitons in the semiconductor layer of OFET memory devices, which can assist the programming/erasing operation with or without external voltage bias. [9,49,50] Therefore, in the erasing process we utilized a white light with light intensity of about 5 mW cm −2 to illuminate the memory device. It was found that the transfer curve shifted back to its initial position (defined as the erased state) after the WG 3 NSs device was illuminated for 1 s. Memory window (ΔV TH ) is an important parameter for memory devices, which is defined as the difference between V TH in the programmed and the erased states.…”
Section: Field-effect Transistor Memorymentioning
confidence: 99%
“…In the light-erasing process, when the memory devices are illuminated, a large amount of excitons are generated in pentacene and then move to the pentacene/ WG 3 interface where charge-exciton annihilation subsequently occurs, resulting in the neutralization of trapped holes in WG 3 (Figure S13b,d, Supporting Information). [49,50] Thus, the transfer curve shifts back to the positive-voltage direction. Interestingly, the energy levels of the WG 3 NSs and the WG 3 film appear to be identical, which indicates the same tunneling barrier with pentacene; however, the memory performance of the WG 3 NSs device is far superior to that of the WG 3 film device.…”
Section: Field-effect Transistor Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, to date, there have been limited systematic studies of photomemory that address the photo‐programming time for effective programming process. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%